Concentric and Eccentric: muscle contraction or exercise? New perspective - Padulo, Johnny (2014)
Universidade Estadual Paulista Júlio de Mesquita Filho, Departamento de Educação Física, Faculdade de Ciências de Bauru, Bauru, Avenida Engenheiro Luiz Edmundo Carrijo Coube, Vargem Limpa, CEP 17033360, SP, Brasil